2012
DOI: 10.1177/1091581812459893
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disposition of the Insect Repellent DEET and the Sunscreen Oxybenzone Following Intravenous and Skin Administration in Rats

Abstract: Insect repellent N,N-diethyl-m-toluamide (DEET) and sunscreen oxybenzone have shown a synergistic percutaneous enhancement when applied concurrently. Both compounds are extensively metabolized in vivo into a series of potentially toxic metabolites: 2 metabolites of DEET, N,N-diethyl-m-hydroxymethylbenzamide (DHMB) and N-ethyl-m-toluamide (ET), and 3 metabolites of oxybenzone, 2,4-dihydroxybenzophenone (DHB), 2,2-dihydroxy-4-methoxybenzophenone (DMB), and 2,3,4-trihydroxybenzophenone (THB). In this study, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Regarding BP-3 metabolism and excretion, no information is available for fish and the majority of the data are for rats. Contrary to TiO 2 NPs, high amounts of BP-3 and its metabolites are found in the kidney [66,67], suggesting excretion through this organ. Nevertheless, in the present study, the kidney's role in the excretion of BP-3 cannot be confirmed.…”
Section: Organ-specific Oxidative Stress Profilesmentioning
confidence: 97%
“…Regarding BP-3 metabolism and excretion, no information is available for fish and the majority of the data are for rats. Contrary to TiO 2 NPs, high amounts of BP-3 and its metabolites are found in the kidney [66,67], suggesting excretion through this organ. Nevertheless, in the present study, the kidney's role in the excretion of BP-3 cannot be confirmed.…”
Section: Organ-specific Oxidative Stress Profilesmentioning
confidence: 97%
“…One of the most widely used dermal PCPs are sunscreen products, which have become an integral part of summer routine for the general population, mainly due to a growing awareness of the risks derived from exposure to the sun. Benzophenone-3 (BP3) or oxybenzone is one of the main substances used as an active ingredient in sunscreens, due to its wellestablished UV-blocking e cacy (Emonet et al 2001;Fediuk et al 2012). BP3 shows clear estrogenic and antiandrogenic effects in vitro, although anti-progesterone and thyroid actions cannot be excluded (Mustieles et al 2023;Schlumpf et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To date, various technologies have been applied to measure the biomedical administration of collagen to skin, including chemical assays (Fediuk et al, 2012), tissue inspection (Schulz et al, 2002), isotope tracing (Cross et al, 2007) and circulating diffusion chamber (Gamer et al, 2006), which can only be used to quantitatively examine the transdermal absorption of exogenous collagen in vitro. However, these approaches could not dynamically track the process of transdermal absorption in vivo and evaluate the real-time effects of biomedical administration.…”
Section: Introductionmentioning
confidence: 99%